Common features in the thermoacoustics of flames and engines - Lawn, Chris J; Penelet, Guillaume (International journal of spray and combustion dynamics, 2018)
Thermoacoustic phenomena generated inadvertently during combustion, and those produced by heating and cooling material to generate a temperature gradient, have mostly been studied independently. Indeed, researchers of one phenomenon are seldom familiar with the literature on the other. This paper seeks to remedy this by reviewing the two subjects alongside one another, by comparing and contrasting them where possible. There is a brief account of the historically important papers in the development of both subjects, followed by a description of the nature of the phenomena. A selective number of papers is called upon to illustrate these principles. Techniques for handling the pure acoustics in the two subjects are addressed, before an outline is given of the modelling of the two thermoacoustic systems. Non-linear phenomena in the two systems are then explored. Finally, methods of ‘control’, of changing the system characteristics, are briefly discussed.